2012
DOI: 10.1079/pavsnnr20127037
|View full text |Cite
|
Sign up to set email alerts
|

Switchgrass - practical issues in developing a fuel crop.

Abstract: The biomass-based energy sector will play an important role in our drive towards renewable energy. Switchgrass has been identified as one of the candidate-dedicated energy crops in the USA because of its various desirable traits. However, many challenges still exist in ensuring a commercially viable switchgrass crop that is sustainable and techno-economically feasible. This article reviews the existing literature to highlight those challenges and potential solutions and recommendations to address those in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 141 publications
(152 reference statements)
0
3
0
2
Order By: Relevance
“…Some of the longer particles of Grind-Sm were also removed, however, less than 10% of the particles were removed by mass, so removing the large particles is not likely to have affected the shear results. [27] Supplementary Figures 18 and 19 display shear strength data similar to Figure 6, except the preshear stress for the measurements are 1 kPa and 7 kPa, respectively. The results at higher preshear stress are similar with the shear strengths of Chop-Sm being lower than that of the other samples.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Some of the longer particles of Grind-Sm were also removed, however, less than 10% of the particles were removed by mass, so removing the large particles is not likely to have affected the shear results. [27] Supplementary Figures 18 and 19 display shear strength data similar to Figure 6, except the preshear stress for the measurements are 1 kPa and 7 kPa, respectively. The results at higher preshear stress are similar with the shear strengths of Chop-Sm being lower than that of the other samples.…”
Section: Resultsmentioning
confidence: 93%
“…Jensen et al measured the bridging tendency of wood chips from whole trees, logging residues, and roundwood cut to different particle sizes and shapes and at different moisture contents using an adjustable slot opening and found that most of the variation was due to the fraction of particles longer than 100 mm and moisture content. [26] Switchgrass (Panicum virgatum L.) has been identified as a potential cellulosic energy crop for biofuel production [27] and, similar to other energy crops, switchgrass poses challenges for harvesting, transportation, storage, and handling. In particular, the low bulk density and poor handling properties of switchgrass prompted the USDOE to award Genera Energy and the University of Tennessee a US$4.9 million grant to develop high-tonnage equipment systems to efficiently supply switchgrass to commercial-scale biofuels facilities, with the unit in Vonore, Tennessee, as an example.…”
Section: Introductionmentioning
confidence: 99%
“…Однією з найперспективніших багаторічних рослин для виробництва біопалива є просо прутоподібне -свічграс (Panicum virgatum L.). Основними перевагами свічграсу, як біоенергетичної культури вважають відносно високий урожай, низьку потребу у воді та підживленні, надійну продуктивність у широкому географічний ареал, зменшена ерозія ґрунту, поглинання вуглецю та покращення середовища існування дикої природи [5].…”
Section: вступunclassified
“…Ґрунтовокліматичні умови України сприятливі для вирощування біоенергетичних культур і вона має великий потенціал створення стабільного ринку енергетичних культур та використання їх сировини для виробництва біопалива [5]. Однією з найперспективніших багаторічних рослин для виробництва біопалива є просо прутоподібне -свічграс (Panicum virgatum L.), основними перевагами якої є відносно висока урожайність, низька потреба у воді та підживленні, надійна продуктивність у широкому географічний ареал, зменшена ерозія ґрунту, поглинання вуглецю та покращення середовища існування природи [6].…”
unclassified